FRI0528 Successful implementation of a pharmacist-led fracture liaison service at a us veteran affairs (VA) hospital. (15th June 2017) - Buehring, B; Holobyn, T; Kotek, J; Glynn-Servedio, B; Wright, S; Hansen, K; Bridges, A
Abstract : Background: Worldwide, an osteoporosis (OP) care gap exists for individuals with a fragility fracture (FF). Published data shows that US veterans are no exception. To address the OP care gap, fracture liaison services (FLS) are being implemented with the goal to prevent additional FF. Objectives: Here we report the patient outcomes after initiating a FLS at a US Veterans Affairs (VA) hospital. Methods: We identified veterans with a pelvic, hip and/or femur shaft fracture by querying a central database. Veterans with traumatic fractures, active OP medication, recent dual-energy X-ray absorptiometry (DXA) and/or hospice status were excluded. The remaining veterans were contacted via letter and the responsible primary health care team was sent a template letter with OP management recommendations via the electronic medical record. Recommendations included DXA, laboratory evaluation, and pharmacologic and non-pharmacologic interventions. In most cases, trained clinical pharmacists serving as FLS coordinators performed all tasks with an expert physician available for questions. Presented data are based on a review 4 months after recommendations were sent. Results: The initial query revealed 149 veterans with pelvic, femoral, and/or hip fractures without a recent DXA and/or active OP therapy. Of those, 32 (31 males, 1 female) patients suffered a FF and were included in the FLS intervention. Our review showed that 59% of these had a DXA scan, 35% had their calcium/vitamin D intake reviewed, and 40% had started OP therapy or were referred to an OP specialist. When the primary care team's clinical pharmacist instead of the primary care provider implemented the FLS recommendations (10/32), 100% of the recommendations were addressed. Furthermore, 70% of patients had a bisphosphonate ordered, whereas it was 9% when no pharmacist was involved (p=0.0004). Conclusions: Our study suggests that a pharmacist-led FLS improves post-FF care in US veterans. We found a high percentage of OP care goals met when patients interacted with clinical pharmacists. This observation might be due to the fact that most pharmacists had dedicated training in OP management and their interaction with the patient focused on their FF. In summary, our data suggests that clinical pharmacists trained in OP management can very effectively implement a FLS intervention. Disclosure of Interest: None declared